1993
DOI: 10.1093/tropej/39.6.346
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Syncytial Virus Infection in Young Children Hospitalized with Respiratory Illness in Riyadh

Abstract: The occurrence of respiratory syncytial virus (RSV) infection among young children hospitalized with lower respiratory tract illness, at King Khalid University Hospital in Riyadh, was examined during the autumn-winter season between September 1991 and February 1992. Sixty-nine cases were diagnosed by immunofluorescent antibody staining of viral antigen in nasopharyngeal aspirates from 127 children, constituting 54 per cent of these patients. Virus culture was attempted only in a few cases, yielding two isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
0
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 0 publications
3
19
0
1
Order By: Relevance
“…A similar pattern has been observed in Saudi Arabia 7 • In this study we found that fever >39°C, toxic ill look, bronchial breathing, WCC > 20xl0 19 /L, neutrophils >5xl0 9 /L, platelet count > 500xl0 9 /L, ESR >45mm/hour, lobar consolidation and pleural effusions were significantly (p>0.005) more frequent in children with bacterial infections. The overall mortality was low (0.25%) probably because in this study the children involved were all nourished, had received immunizations, none had underlying diseases, and had easy accessibility to health care facilities in Kuwait.…”
supporting
confidence: 87%
“…A similar pattern has been observed in Saudi Arabia 7 • In this study we found that fever >39°C, toxic ill look, bronchial breathing, WCC > 20xl0 19 /L, neutrophils >5xl0 9 /L, platelet count > 500xl0 9 /L, ESR >45mm/hour, lobar consolidation and pleural effusions were significantly (p>0.005) more frequent in children with bacterial infections. The overall mortality was low (0.25%) probably because in this study the children involved were all nourished, had received immunizations, none had underlying diseases, and had easy accessibility to health care facilities in Kuwait.…”
supporting
confidence: 87%
“…17 Our data demonstrate that there was seasonal activity associated with RSV subgroup A which was isolated throughout the study period during the coldest months of the year. In successive years, the incidence tended to alternate between an early peak and a late peak.…”
Section: Discussionmentioning
confidence: 50%
“…Pneumonia accounted for 4336 patients (73.3% of ALRTI admissions) ( Table 2), which is lower than the 86.5% reported in a Bangladesh study. 24 Bronchiolitis accounted for 1581 patients (26.7% of ALRTI admissions), which is lower than the 35% and 54% reported earlier in South India 25 and Riyadh, 26 respectively. Better immunization, nutrition, socioeconomic and educational status at present could explain the lower incidence of both pneumonia and bronchiolitis in our study, compared to eight years ago when these two studies were performed (from 1985 to 1987).…”
Section: Discussionmentioning
confidence: 77%
“…The higher male to female ratio (1.4:1) in this study has been reported in other studies. 18,[24][25][26] Although bronchiolitis and pneumonia have been shown in this study to be present throughout the year, there is a clear correlation with the rainy season starting in our area in October through March, with a peak in January (Table 3). This is consistent with earlier studies from other tropical and Western countries.…”
Section: Discussionmentioning
confidence: 85%